Hepatocellular Carcinoma Differentiation: Research Progress in Mechanism and Treatment - Song, Jianning; Zhou, Hongzhong; Gu, Dayong; Xu, Yong (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver. Although progress has been made in diagnosis and treatment, morbidity and mortality continue to rise. Chronic liver disease and liver cirrhosis are still the most important risk factors for liver cancer. Although there are many treatments, it can only be cured by orthotopic liver transplantation (OLT) or surgical resection. And the worse the degree of differentiation, the worse the prognosis of patients with liver cancer. Then it can be considered that restoring a better state of differentiation may improve the prognosis.The differentiation treatment of liver cancer is to reverse the dedifferentiation process of hepatocytes to liver cancer cells by means of drugs, improve the differentiation state of the tumor, and restore the normal liver characteristics, so as to improve the prognosis. Understanding the mechanism of dedifferentiation of liver cancer can provide ideas for drug design. Liver enrichment of transcription factors, imbalance of signal pathway and changes of tumor microenvironment can promote the occurrence and development of liver cancer, and restoring its normal level can inhibit the malignant behavior of tumor.At present, some drugs have been proved to be effective, but more clinical data are needed to support the effectiveness and reliability of drugs. The differentiation treatment of liver cancer is expected to become an important part of the treatment of liver cancer in the future.